Perilaku Biokimia Benih Kedelai Selama Penyimpanan dalam Kondisi Terkontrol - Noviana, Irma; Qadir, Abdul; Suwarno, dan Faiza Chairani (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTPhysiological and biochemical changes in seeds indicates levels of viability and vigor during deterioration. The aims of the research were to study the patterns of biochemical changes in soybean seeds and its relationship to seed vigor during storage under controlled conditions. The experiment was arranged in a completely randomized design using two varieties as a factor which was nested into storage period and replicated four times. Two varieties were Gepak Kuning and Mallika, stored in controlled condition at temperature of 19-22 °C and 64-67% of relative humidity for six months. The seeds were evaluated for protein, peroxide value, electrical conductivity and seed viability. The exponential regression analysis was used to determine the patterns of biochemical changes of each soybean varieties during the storage period. The results showed that the biochemical behaviour of soybean seeds stored under controlled conditions for 24 weeks following the exponential equation of y = a + b expcx, which a, b, and c were constants that has different value for each variety. Electrical conductivity and peroxide value could be used as indicators of seed vigor during storage under controlled conditions for 24 weeks. Seed storage under controlled conditions are to maintain seed vigor >80% up to 12 weeks for Mallika and 24 weeks for Gepak Kuning with low oxidative process and less membrane damages.Keywords:deterioration, storability, vigor